PENGARUH HARD SKILL DAN SOFT SKILL TERHADAP KINERJA KARYAWAN PT. TELKOM SUMATERA - Novita Sari Siahaan; Humisar Sihombing (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2017)
This study aims to determine the effect of Hard Skill and Soft Skill Against Employee Performance PT. Telkom Sumatera. The sample in this research is all employees of PT. Telkom Sumatra as many as 67 people. The test used is instrument test and classical assumption test. Hypothesis testing using multiple linear regression analysis, t test and F test. From result of validity test obtained rcount > rtable for each question item and reliability test questionnaire obtained by alpha cronbach each variable that is 0,826 for variable of Hard Skill (X1), 0,897 for variable of Soft Skill (X2) and 0,885 for Employee Performance variable Y). This value is greater than the significant level of rtable is 0.313. Data analysis of each variable obtained by regression equation Y = 14,154 + 0,330 X1 + 0,387 X2 + e. Obtained R2 equal to 0,521 which means X1, X2,  explain the effect to Y variable equal to 52,1% while the rest influenced by other factor. The partial test (t test) of each independent variable has an effect on the dependent variable with the research significance is smaller than 0,1, and the result of simultaneous test (test F) calculation is 34,784 with Ftable 2,38 which means Fcount> Ftable with level if significant (α) <0, 1, which means the accepted hypothesis is Hard Skill and Soft Skill has jointly significant effect on Employee Performance PT. Telkom Sumatera. Keywords: Hard Skill, Soft Skill, Employee Performance